2020
DOI: 10.1186/s12870-020-02508-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and integrated analysis of lncRNAs in rice backcross introgression lines (BC2F12)

Abstract: Background: Distant hybridization is an important way to create interspecific genetic variation and breed new varieties in rice. A lot of backcross introgression lines (BILs) had been constructed for the scientific issues in rice. However, studies on the critical regulatory factor lncRNA in cultivated rice, wild rice and their BIL progenies were poorly reported. Results: Here, high-throughput RNA sequencing technology was used to explore the functional characteristics and differences of lncRNAs in O. sativa, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…In recent years, studies on plant ncRNAs have mainly focused on lncRNAs, circRNAs and miRNAs ( Dou et al, 2017 ; Wang et al, 2018 , 2021c ; Li et al, 2020 ; You et al, 2021 ; Zhou et al, 2021 ). Due to the differences in the sources and functions of these three types of ncRNAs, they play a role in various plant growth and development processes ( Voinnet, 2009 ; Tang and Chu, 2017 ; Zhai et al, 2020 ; Chand Jha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies on plant ncRNAs have mainly focused on lncRNAs, circRNAs and miRNAs ( Dou et al, 2017 ; Wang et al, 2018 , 2021c ; Li et al, 2020 ; You et al, 2021 ; Zhou et al, 2021 ). Due to the differences in the sources and functions of these three types of ncRNAs, they play a role in various plant growth and development processes ( Voinnet, 2009 ; Tang and Chu, 2017 ; Zhai et al, 2020 ; Chand Jha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of lncRNA LAIR increases rice grain yield and upregulates some neighboring gene expression ( Wang et al, 2018 ). Parental expression level dominance lncRNAs were identified in rice backcross introgression lines ( Li et al, 2020 ), but lncRNA expression profile and the important role of lncRNA in heterosis formation of inter-subspecific hybrid rice need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…NcRNA includes microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and so on, which have emerged as key regulators of gene expression through their direct and indirect actions on chromatin [23][24][25]. In Oryza sativa, 1,254 differentially expressed lncRNAs (DELs) were identified from BIL progenies [26]. Another RNA-Seq showed that 328 of 444 DELs were associated with meiosis and the low fertility in autotetraploid rice [27].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their genomic location, lncRNAs are classified into three major categories, including long intergenic non-coding RNA (lincRNA), long non-coding natural antisense transcripts, and long intronic non-coding RNA ( Cui et al, 2017 ). The functional roles of lncRNAs in plants are increasingly being unraveled, and a number of various reports associated with identification of lncRNAs in multiple plant species ( Wang and Chekanova, 2017 ), including Zea mays ( Li et al, 2014 ; Kim et al, 2019 ), Solanum lycopersicum ( Cui et al, 2020 ), Arachis hypogaea ( Zhao et al, 2019 ; Tian et al, 2020 ), Oryza sativa ( Li et al, 2020 ), Populus ( Ma et al, 2019 ), and Arabidopsis thaliana ( Zhao et al, 2018 ), have been published. However, most experimental proofs focus on the functions of lncRNAs associated with plant development and abiotic stress responses, such as fruit ripening ( Li et al, 2018 ; Yu et al, 2019 ), growth ( Meng et al, 2018 ; Wang Y. et al, 2018 ), nutritional stimulation ( Wang et al, 2017 ), and salt and drought stresses ( Qin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%